Psychology and life - Gerrig, Richard J
Includes answer appendix and glossary.; Includes bibliographical references (pages R-1-R-47) and indexes.; Brief contents: 1. Psychology and life -- 2. Research methods in psychology -- 3. The biological and evolutionary bases of behavior -- 4. Sensation and perseption -- 5. Mind, consciousness and alternate states -- 6. Learning and behavior analysis -- 7. Memory -- 8. Cognitive Processes -- 9. Intelligence and intelligence assessment -- 10. Human development across the life span -- 11. Motivation -- 12. Emotion, stress, and health -- 13. Understanding human personality -- 14. Psychological disorders -- 15. Therapies for psychological disorders -- 16. Social cognition and relationships -- 17. Social processes society and culture.